Efforts To Improve Students’ Disciplinary Character Through Religious Habituation At Darut Taqwa Vocational High School - Ahmad Ega Nurul Ishaq; Ahmad Ma’ruf (P3M STAI Kuningan, 2026)
Background: Character education is a primary objective of Indonesia’s national education system. However, empirical evidence on the effectiveness of religious habituation in strengthening students’ disciplinary character, particularly in vocational schools, remains limited. Objective: This study aims to examine the role of religious habituation as a strategy for strengthening students’ disciplinary character at SMK Darut Taqwa. Method: This study employed a qualitative descriptive approach during the odd semester of the 2024/2025 academic year. Data were collected through observations, semi-structured interviews, and documentation involving seven purposively selected informants. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while validity was ensured through source and technique triangulation. Findings and Implications: The findings indicate that religious habituation activities, including Qur’an recitation, congregational Duha and Dhuhr prayers, collective supplication, and a greeting culture, positively strengthened students’ punctuality, compliance with school regulations, responsibility in completing assignments, and participation in school activities. Teacher role modeling, a supportive religious environment, and strong school–parent collaboration emerged as key enabling factors. Conclusion: Religious habituation is an effective and context-sensitive strategy for fostering disciplinary character in pesantren-based vocational schools and should be systematically integrated into character education programs.